Strategi Pengelolaan Perpustakaan Sekolah dalam Mengembangkan Minat Membaca Siswa di Madrasah Ibtidaiyah - Hidayati, Sefa; Botifar, Maria; Khair, Ummul (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Reading has a very important role for student success, but various reviews that have been carried out show that students' interest in reading in Indonesia is still low. Purpose of this study was to determine the school management strategy, to determine student reading interest, and to determine the school library management strategy in developing student reading interest at MIS GUPPI No. 13 Lake Malaya. Type of research is a qualitative research and data collection methods in the form of observation, interviews, and documentation. Subjects of this study were the principal madrasah, school library managers, and students. Data analysis starts from data reduction, data presentation and drawing conclusions. Results of this study are the school library management strategy at MIS GUPPI No. 13 Tasik Malaya, namely: strategies for managing library collections and strategies for classifying and cataloging library materials. Interest in reading students at MIS GUPPI No. 13 Tasik Malaya Malaya is still experiencing instability and still needs to be redeveloped. To develop students' interest in reading, library managers carry out several strategies, namely: updating library collections, giving gifts to students who are diligent in visiting the library, and involving the role of parents and the student's family environment.